2004
DOI: 10.1126/science.1095139
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric New Particle Formation Enhanced by Organic Acids

Abstract: Atmospheric aerosols often contain a substantial fraction of organic matter, but the role of organic compounds in new nanometer-sized particle formation is highly uncertain. Laboratory experiments show that nucleation of sulfuric acid is considerably enhanced in the presence of aromatic acids. Theoretical calculations identify the formation of an unusually stable aromatic acid-sulfuric acid complex, which likely leads to a reduced nucleation barrier. The results imply that the interaction between organic and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
693
4
12

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 766 publications
(730 citation statements)
references
References 31 publications
15
693
4
12
Order By: Relevance
“…The catalytic effect of incorporating organic acids into sulfuric acid aerosol models has been verified through laboratory experiments. 64 …”
Section: Resultsmentioning
confidence: 99%
“…The catalytic effect of incorporating organic acids into sulfuric acid aerosol models has been verified through laboratory experiments. 64 …”
Section: Resultsmentioning
confidence: 99%
“…These species are products of photochemical oxidation of volatile organic precursors on these pre-existing nuclei (O'Dowd et al, 1999;Kulmala et al, 2004). In fact, recent studies by Zhang et al (2004) showed that nucleation rates of sulfuric acid are greatly increased in the presence of organic acids (including products of atmospheric photochemical reactions), by forming unusually stable organic-sulfuric acid complexes, thereby reducing the nucleation barrier of sulfuric acid. It is interesting to note in our field measurements that summertime levels of ultrafine particles at source sites, such as long Beach and USC peaked in midday (i.e., noon to 1300), whereas ultrafine PM numbers peak slightly later (i.e., between 1500 and 1600) in the inland receptor sites.…”
Section: Discussionmentioning
confidence: 99%
“…For example, theoretical calculations and observations [Barsanti et al, 2009;Kurten et al, 2008;Smith et al, 2008Smith et al, , 2010 have shown that amines may be involved in J is nucleation rate calculated from PARGAN (that is, J PARGAN ), C is preexponential factor, and P is power, for J = C[H aerosol nucleation in the atmosphere. Laboratory studies also showed that aromatic acids may increase nucleation rates similarly to NH 3 [Zhang et al, 2004] and biogenic organic compounds can enhance aerosol growth rates of H 2 SO 4 aerosols [Zhang et al, 2009].…”
Section: Indirect Chemical Information Of Newly Formed Particlesmentioning
confidence: 99%